PHENOMENOLOGY STUDY: RESILIENCE EXPERIENCE OF FARMER AFTER ERUPTION OF KELUD MOUNTAIN IN 2014 IN PUNCU VILLAGE OF PUNCU DISTRICT KEDIRI DISTRICT - Lilik Setiawan; Retty Ratnawati; Retno Lestari (NurseLine Journal, 2017)
The eruption of the volcano resulted in material damage, loss of life, environmental damage, and psychological impact. The psychological impact of Mount eruption is one that needs attention for psychological impact that can lead to Post traumatic Stress Disorder (PTSD). The purpose of study was to explore resilience experience of farmer after eruption of Kelud Mountain in 2014 in Puncu village of Puncu district, Kediri. The research design was qualitative with interpretive phenomenology approach. Data collection used in-depth interview method through semi-structured interview guide involving six participants and analysis was conducted with interpretive phenomenology analysis (IPA). This research produced nine themes including: 1) feel comfortable to live in kelud montain slope, 2) believing mounth activity can be unpredictable, 3) Believes the eruption brings blessings, 4) Feeling in a state of degradation 5) Accepting reality, 6) Trying to rise from difficult situation, 7) Looking for peace of mind, 8) Hoping for good disaster management, 9) Reviving community tradition. The role of health personnel in providing services to farmers affected by eruption of the mountain is needed so that they can understand, live and accept the conditions adaptively.